Keterlibatan Perempuan dalam Perang, Politik dan Non-Politik Menurut Perspektif Islam (Studi Kasus: Perlawanan Perempuan Palestina terhadap Okupasi Israel Tahun 2000-2019) - Rachmawati, Tety; Karisma, Gita; Mumtaz, Sonya (POLITEA, 2022)
Israel's occupation of Palestine led to resistance by the Palestinian people from all over the country. This struggle is not only carried out by men but also women. In the Islamic perspective, women and men have the same position, there is no discrimination between them. This paper aims to explain the resistance of Palestinian women to Israeli occupation based on an Islamic perspective. The research used qualitative methods through literature study. The results of this research indicate that the Palestinian women's resistance emphasizes the equal position of men and women in Islam. Islam does not limit the roles and activities of women. In conflict situations, women are allowed to participate in war and also in politics. Resistance of Palestinian women to Israeli occupation is carried out in two ways, namely direct and indirect resistance. The direct resistance is carried out by Palestinian women through war and politics. Meanwhile, indirect resistance is carried out by providing education for children about the values of the Islamic struggle.